2020
DOI: 10.3167/fcl.2020.012804
|View full text |Cite
|
Sign up to set email alerts
|

Financialization from the margins

Abstract: AbstractThis article investigates how the Argentine subproletariat perceives the recent consumer credit boom, based on several field visits carried out in one of Argentina's industrial hubs between 2007 and 2016. It analyzes the credit boom in relation to the wider social transformations induced by the leftist Peronist governments during 2003–2015 (especially the incorporation of informal workers into the social protection system). It argues the rise of consumer credit is perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…However, the relentless requirements of finance are often at odds with the insecurity and precarity that characterize income streams of the poor. As Saiag (2020) has shown in Argentina, the time demands of finance in the form of credit repayments are not always reconcilable with the time patterns of work, particularly in instances where people are precariously employed. This resulted in a feeling of losing control over one's time due to credit taking — where finance, and not the individual, ‘dominates the time of labour’ (Saiag, 2020: 24).…”
Section: Financial Inclusion: Interrogating Infrastructurementioning
confidence: 99%
See 1 more Smart Citation
“…However, the relentless requirements of finance are often at odds with the insecurity and precarity that characterize income streams of the poor. As Saiag (2020) has shown in Argentina, the time demands of finance in the form of credit repayments are not always reconcilable with the time patterns of work, particularly in instances where people are precariously employed. This resulted in a feeling of losing control over one's time due to credit taking — where finance, and not the individual, ‘dominates the time of labour’ (Saiag, 2020: 24).…”
Section: Financial Inclusion: Interrogating Infrastructurementioning
confidence: 99%
“…As Saiag (2020) has shown in Argentina, the time demands of finance in the form of credit repayments are not always reconcilable with the time patterns of work, particularly in instances where people are precariously employed. This resulted in a feeling of losing control over one's time due to credit taking — where finance, and not the individual, ‘dominates the time of labour’ (Saiag, 2020: 24). Put simply, the ceaseless demands of debt repayment rendered those with insecure incomes even more precarious, increasing their exposure to risk.…”
Section: Financial Inclusion: Interrogating Infrastructurementioning
confidence: 99%
“…Accounts highlight how the ceaseless demands of microfinance repayments often deepen livelihood insecurity, given the discrepancy between irregularity of income and demands for regular repayments. This can lead debtors to feel they are losing control over their lives (Saiag, 2020). Ensuing insecurity has a gendered inflection as Paprocki (2016) identifies: ‘with the proliferation of microcredit lending, women's responsibilities for household labor persist and remain invisible, while their gendered role as microcredit borrowers becomes the basis of their further social and economic dispossession’ (p. 33).…”
Section: Rural Autonomy Land and Gendermentioning
confidence: 99%
“…12 This means that households with poor income-generating prospects are able to take on multiple loans, or loans that far exceed their income capacity. The rigidity of repayment schedules jar with the insecure and temporally diffuse nature of available work, hence leading to what Saiag ( 2020 , 23) terms ‘the mismatch between the time of labor and the time of finance’. Furthermore, acceptable forms of collateral have also been deregulated.…”
Section: ‘Not-decent-enough Work’: Microfinance-dependency and Sacrifice In The Garment Sectormentioning
confidence: 99%
“…Duvendack and Mader (2019: 7), in their systematic review, found that 'the effects of financial services on core economic poverty indicators such as incomes, assets or spending, and on health status and other social outcomes, are small and inconsistent'. Furthermore, far from the promised beneficial outcomes, microfinance has often been called into question for increasing the reliance of marginalized and lowincome workers, as well as unemployed or underemployed people, on credit for social reproduction (e.g., Soederberg, 2014;Taylor, 2012), reproducing inequalities and, specifically, unequal gender relations (e.g Kar, 2018;Roberts, 2015;Young, 2010), as well as causing extreme stress to its users (e.g., Rankin, 2013). This paper contributes to this critical literature on microfinance and further problematises the links between this development project and labour conditions.…”
Section: The Financial Inclusion-decent Work Nexus: a Challengementioning
confidence: 99%